Characterization and properties of miswak (Salvadora persica L.) fiber-reinforced polylactic acid biocomposites - Ahmad Fazil, Nur Diyana (2023)
The characterization and properties prepared from miswak fiber (MF)/polylactic acid (PLA) using internal mixer and compression molding was investigated. The chemical, physical, and thermal properties of untreated and alkali-treated fiber biocomposite were all examined. The aspect ratio and fiber density were found to be exceptionally low. While alkaline treatment exposes a clean and clear fiber surface, untreated fiber's shape indicates the existence of residual material. The TGA statistics demonstrate the thermal resilience of fiber because its quality only starts to decline at 88°C. Contrarily, alkaline treatment raises fiber thermal stability to 96°C. Miswak fiber content significantly affected the mechanical and physical properties of MF/PLA composites as higher loading increased the density, water absorption and thickness swelling. The 10wt% fiber loading (M1) in PLA showed highest tensile strength (33.7 MPa) and highest modulus (2.9 GPa), respectively. In all composites, M1 composite have better crystallization and melting temperatures at 95°C and 139°C as well as better thermal stability when the maximum degradation occurs at 341°C. DMA noticed that the addition of miswak fiber increased E' curve and slightly shifted Tan δ to a lower temperature. As compared to PLA matrix, the biodegradability of the composites was superior as deterioration was observed after 100 days in soil burial test. As for alkali treated composites properties, the FTIR shows constant shift as the alkali concentration increases up to 3%. Tensile modulus results show mechanical performance increase from 1% to 3% with 30 wt.% fiber loading and SEM micrograph supported the tensile results. The alkali treated fiber composites exhibit better thermal stability as TGA curve showed slightly to high temperature as compared to untreated fiber composites and DSC curve showed improved in crystallization temperature for alkali treated fiber composites recorded at highest 116°C for 1% alkali concentration. The DMA found that adding alkali treated fiber in PLA affected the level of storage modulus curve and Tan δ peak magnitude analysis results also showed the 1% alkali-treated fiber had better adherence to the MF/PLA matrix. In conclusion, composites with 10wt% of miswak fibre loading in PLA showed better in overall properties. Moreover, 1% alkali treated fiber/PLA composites showed increase thermal stability among the other alkali concentration with 10wt.% fiber loading. Hence the M1 composites would be very suitable for light density and good mechanical and thermal properties area for variety of potential application.